Karakteristik Sosial-Ekonomi dan Produktivitas Tenaga Kerja Panen Kelapa Sawit PT Task Parenggean - Gilang Dio Pratama; Rhina Uchyani Fajarningsih; Sri Marwanti (Jurnal Ilmu Pertanian Indonesia, 2024)
This study aims to describe the characteristics of the oil palm harvest workforce and socio-economic factors related to the productivity of harvesting labor at PT Task Parenggean. The sample was taken from the harvest labor population of Estate 1, Estate 2, and Estate 3, represented by 95 workers. The data were analyzed using multiple linear regression analysis and processed using SPSS (Statistical Program for Science). The results showed that age, family dependents, work experience, facilities & and infrastructure, and salary significantly affected the productivity of oil palm harvesting workers at PT Task Parenggean. In contrast, the level of education, residence, and premiums had no significant effect. Keywords: socioeconomic, labor productivity, palm oil